IMPLEMENTATION OF COMMUNITY BASED TOURISM IN MANAGING COMPETITIVE TOURIST VILLAGES: A QUALITATIVE STUDY OF KUTUH TOURIST VILLAGE - I Wayan Chandra Adyatma; I Made Dwi Sumba Wirawan; I Made Dwi Harmana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The development of community-based tourism villages is an important strategy for realizing sustainable and competitive tourism. The Community-Based Tourism (CBT) approach positions local communities as the primary actors in tourism management, including planning, implementation, and utilization of tourism products. This study aims to analyze the implementation of Community-Based Tourism in the management of Kutuh Tourism Village, Badung Regency, Bali Province, and to examine the role of the community, governance dynamics, and the contribution of CBT to the competitiveness of tourism villages. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation studies involving village governments, traditional villages, tourism village managers, Pokdarwis (tourism group groups), MSMEs, and community leaders as research informants. Data analysis was conducted using thematic analysis to identify key patterns and themes related to CBT implementation. The results show that CBT implementation in Kutuh Tourism Village has been ongoing, but is not yet fully optimal. Community participation is more dominant in the operational aspects of tourism, while involvement in strategic decision-making is still limited. The governance of tourism villages shows the dominance of certain actors, which has implications for limited space for community participation and the unequal distribution of tourism economic benefits. Nevertheless, the implementation of CBT contributes to increasing the competitiveness of tourist villages by strengthening local cultural identity and community involvement in tourism activities. This study concludes that strengthening community participation, enhancing human resource capacity, and improving more inclusive and transparent governance are essential prerequisites for optimizing the implementation of Community-Based Tourism in enhancing the competitiveness and sustainability of tourist villages.